COMPARATIVE IN VIVO STUDY OF TWO DIFFERENT ROUTES: ORAL AND TRANSCRANIAL FOR THE EFFECT OF POLYPHYTO NOOTROPIC FORMULATION FOR ITS MEMORY ENHANCING PROPERTIES - Shib Nath Kamila; N.V. Satheesh Madhav; Chandra Nath Sarkar (International Journal of Phytomedicine, 2014)
The present study objective is to comparing the effectiveness of the medhya (polyphyto) formulations for its learning and memory activity in two different routes oral and transcranial;could be delivered and targeted to the brain by transcranial delivery route. The unique anatomical arrangement of blood vessels and sinuses in the human skull and the brain, the prevalence of a high density of skin appendages in the scalp, extra cranial vessels of the scalp communicating with the brain via emissary veins and most importantly, the way that the scalp is used in the Ayurvedic medical system in treating diseases associated with the brain show that a drug could be transcranially delivered and targeted to the brain through the scalp. The medhya formulation FMLM; compose of Bacopa monnieri (51.8%), Oscimum sanctum (26.7 %), and Withania somnifera (21.5%) on memory acquisition and retention was studied using Elevated plus maze, Morris water maze (MWM) and Pole Climbing apparatus (PCA) in rat using two different routes, one is per oral (FMLMO) and other one is transcranial (FMLMT). As per the result, on administration of polyherbal formulations FMLMO and FMLMT showed significant (p<0.01) reduction in transfer latency in EPM, MWM and escape latency in PCA test as compared with the control per oral as well as transcranial delivery; whereas trancranially applied FMLMT is equally effective in comparison to standard drug but it is shown an extremely significant (p<0.001) effect compared to control group